ANALISIS YURIDIS PERJANJIAN KAWIN TERHADAP PENYELESAIAN HARTA PERKAWINAN DALAM PERKARA CERAI (STUDI PUTUSAN PENGADILAN TINGGI AGAMA NOMOR : 420/PDT.G/2021/PTA SMG.) - Rita Rosita; Sifa Mulya Nurani (KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The phenomenon of a surge in conflicts related to the distribution of assets after divorce is the main trigger for the implementation of this study, in addition to the crucial guarantee of legality related to the position and validity of prenuptial agreements in the positive legal order in Indonesia. The main target of this research is to dissect the position as well as the validity of the marriage agreement. In addition, this research intends to evaluate the basis of juridical arguments used by the panel of judges when resolving cases of distribution of household assets, by referring to the Decision of the High Court of Religion Number 420/Pdt.G/2021/PTA Smg. The researcher applies normative juridical legal research methods through three forms of orientation, namely the regulatory approach, the conceptual approach, and the approach to concrete cases. All secondary data were collected through literature review techniques to be analyzed using qualitative analysis methods. The findings of the study prove that prenuptial agreements that have completed all the criteria for contract validity have strong juridical coercive power to establish joint asset ownership. On the other hand, legal reasoning by judges relies on aspects of the legality of the deed, applicable regulations, and the principles of certainty, justice, and legal protection when deciding the case of the seizure of the property. In conclusion, the marriage contract plays a vital role in creating regulatory guarantees for the governance of material ownership of husband and wife. Therefore, the court needs to maintain continuity in enforcing this rule, accompanied by the expansion of subsequent studies related to the dynamics of the execution of marriage agreements in the reality of the national judiciary. Abstrak. Fenomena lonjakan konflik terkait distribusi aset pasca perceraian menjadi pemicu utama pelaksanaan studi ini, di samping krusialnya jaminan legalitas terkait posisi serta validitas kesepakatan pranikah dalam tatanan hukum positif di Indonesia. Target utama penelitian ini adalah membedah posisi sekaligus keabsahan dari ikatan perjanjian perkawinan tersebut. Selain itu, riset ini bermaksud mengevaluasi dasar argumentasi yuridis yang digunakan oleh majelis hakim sewaktu menyelesaikan perkara pembagian aset rumah tangga, dengan mengacu pada Putusan Pengadilan Tinggi Agama Nomor 420/Pdt.G/2021/PTA Smg. Peneliti menerapkan metode riset hukum yuridis normatif melalui tiga bentuk orientasi, yaitu pendekatan regulasi, pendekatan konseptual, dan pendekatan terhadap kasus konkret. Seluruh data sekunder dihimpun lewat teknik penelaahan literatur pustaka untuk kemudian diurai menggunakan metode analisis kualitatif. Temuan studi membuktikan bahwa kesepakatan pranikah yang telah melengkapi seluruh kriteria keabsahan kontrak mempunyai daya paksa yuridis yang kuat untuk menetapkan kepemilikan aset bersama. Di sisi lain, penalaran hukum oleh hakim bersandar pada aspek legalitas akta, regulasi yang berlaku, serta asas kepastian, keadilan, dan proteksi hukum sewaktu memutus perkara perebutan harta tersebut. Kesimpulannya, kontrak perkawinan memegang andil vital dalam menciptakan jaminan regulasi atas tata kelola kepemilikan materiil suami-istri. Oleh sebab itu, pengadilan perlu menjaga kesinambungan dalam menegakkan aturan ini, disertai perluasan studi berikutnya terkait dinamika eksekusi perjanjian perkawinan dalam realitas peradilan nasional.